2019
DOI: 10.1093/jac/dkz164
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted and Republished: A random survey of the prevalence of falsified and substandard antibiotics in the Lao PDR

Abstract: Objectives In 2012, a stratified random survey, using mystery shoppers, was conducted to investigate the availability and quality of antibiotics sold to patients in the private sector in five southern provinces of the Lao People’s Democratic Republic (Laos). Methods A total of 147 outlets were sampled in 10 districts. The active pharmaceutical ingredient (API) content measurements for 909 samples, including nine APIs (amoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
0
23
3
Order By: Relevance
“…Examples include ciprofloxacin eye drops in India, which had API content 16% to 36% below the acceptable range 17 and ciprofloxacin oral suspensions in Ghana, which only had 67% and 72% API content 18 . A recent study from Laos found that the percent API of antibiotics tested, including ciprofloxacin, spanned a range between 75% and 125% 19 . Substandard antibiotics may also have other issues than low API content such as impurities, poor-quality excipients, or degradation products which all may serve as their own stressors and impact the cells' response and development of resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include ciprofloxacin eye drops in India, which had API content 16% to 36% below the acceptable range 17 and ciprofloxacin oral suspensions in Ghana, which only had 67% and 72% API content 18 . A recent study from Laos found that the percent API of antibiotics tested, including ciprofloxacin, spanned a range between 75% and 125% 19 . Substandard antibiotics may also have other issues than low API content such as impurities, poor-quality excipients, or degradation products which all may serve as their own stressors and impact the cells' response and development of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It is less clear what happens upon repeated exposure to a range of constant sub-inhibitory antibiotic concentrations. This is relevant as substandard antibiotics have been found to have a wide distribution of API content [17][18][19] . Our aim was to determine the role of exposure to different sub-lethal antibiotic concentrations on bacterial antibiotic resistance development.…”
mentioning
confidence: 99%
“…This result exemplifies the possibility of selecting resistance to antibiotics of clinical relevance even in environments not polluted by them. Besides these non-clinical situations, it should not be disregarded that, in certain regions, poorquality medicines, which harbour a substandard quantity of API, are being used in clinics, being precisely the case of ciprofloxacin and tetracycline (Frimpong et al 2018;Johnston and Holt 2014;Tabernero et al 2019). Then, this reality enlarges the variety of circumstances under which AR selection mediated by low antimicrobial concentrations could be befalling.…”
Section: Discussionmentioning
confidence: 99%
“…It is pointed out by heads of state and the WHO that universal health coverage (UHC, Good Health and Well-being) as described in Sustainable Development Goal 3.8 (SDGs) cannot be achieved without ensuring the quality of medicines. In many countries, especially low- and middle-income countries (LMICs), medicine regulation authorities, manufacturers, and researchers are struggling to prevent the distribution of SFMs ( Lon et al, 2006 , Amin and Kokwaro, 2007 , Gaudiano et al, 2007 , Khan et al, 2010 , Khan et al, 2011a , Khan et al, 2011b , Binagwaho et al, 2013 , Yoshida et al, 2014 , Otte et al, 2015 , Petersen et al, 2017 , Yong et al, 2015 , Kakio et al, 2017 , Khuluza et al, 2017 , Kakio et al, 2018 , Pisani et al, 2019 , Tabernero et al, 2019 , Schäfermann et al, 2020 ). However, the prevalence of SFMs is currently increasing globally, especially in LMICs, where the proportion of SFMs has reached 10.5% of the pharmaceutical market ( WHO, 2018 ).…”
Section: Introductionmentioning
confidence: 99%